The Halal Field: Piety Signaling, Symbolic Boundaries, and the Market-Mediated Stratification of Urban Indonesia - Bimala Putri; Fitriyanti Fitriyanti; Henry Peter Paul; Harun Urrashid (Open Access Indonesia Journal of Social Sciences, 2025)
Indonesia's mandatory Halal certification policy represents a critical juncture of state governance, religious practice, and neoliberal market forces. This study moves beyond a purely economic or policy-based analysis to investigate how this regulation functions as a powerful engine of social stratification. We examine the process by which Halal certification creates a new social field of consumption, reshaping class distinctions and religious expression in urban Indonesia. A mixed-methods sequential explanatory design was employed in Jakarta and Makassar. The quantitative phase involved a survey of 500 urban consumers selected via multi-stage stratified sampling. Key variables, including Socio-Economic Status (SES) and Religiosity, were constructed as composite indices. Logistic regression and a Two-Step Cluster Analysis, justified by Bayesian Information Criterion (BIC) and silhouette coefficients, were used to identify consumer patterns. The qualitative phase comprised 30 in-depth semi-structured interviews and over 100 hours of participant observation, with a specific focus on the gendered dynamics of consumption. Quantitative analysis reveals that SES is the strongest predictor of willingness to pay a premium for Halal-certified products (OR=2.89, p<0.001). Cluster analysis identified three distinct consumer profiles: the 'Conscious Cosmopolitans', 'Pious Pragmatists', and 'Market Traditionalists'. Qualitative findings illuminate how the Halal logo has been symbolically transformed from a religious marker into a signifier of quality, modernity, and class. This enables "piety signaling," a gendered performance of social status. In conclusion, Halal certification is not a neutral regulatory tool but an active force in social structuration. It creates a new field of distinction where "Halal capital" is used to perform symbolic boundary-work, legitimizing inequality through the moral language of piety. This study contributes a novel theoretical framework for understanding how state-regulated religion intersects with consumer capitalism to forge new, intersectional hierarchies of class and gender in the contemporary Muslim world.